A systematic mapping review of links between handling wild meat and zoonotic diseases - Tumelty, L.; Fa, J.E.; Coad, L.M.; Friant, S.; Mbane, J.; Kamogne, C.T.; Tata, C.Y.; Ickowitz, A. (Elsevier, 2023)
1. Hunting, trade, and consumption of wildlife present a serious threat to global public health as it places humans in close contact with zoonotic pathogens. 2. We systematically mapped the literature on wild meat handling and zoonotic disease transmission (1996–2022) using the online database Web of Science and Google search engine and identified 6229 articles out of which 253 were finally selected for use in our mapping review; 51 of these provided specific information regarding transmission risks. 3. The reviewed studies reported 43 zoonotic pathogens (17 bacteria, 15 viruses, and 11 parasites) that could pose a potential risk to human health. 4. Sixteen hygienic and sanitary behaviours were described in the reviewed studies. Disease surveillance was the most frequent. Most of the surveillance studies were carried out in Europe and were less common in the tropics. 5. To inform policy and practical actions effectively, it is imperative to broaden our understanding of how various mitigation behaviours can be employed to minimize the risk of transmission.